(untitled) (American Journal of Business Management, Economics and Banking, 2024)
Monetary aggregates play a crucial role in understanding the financial landscape of any economy, serving as key indicators of its monetary policy effectiveness and economic health. In the European context, where monetary policy decisions are shared among multiple countries within the Eurozone, analyzing monetary aggregates becomes even more significant. This article delves into the concept of monetary aggregates and examines their relevance in the context of European countries.